Identifying strategies for mitigating the global warming impact of the EU-25 economy using a multi-objective input–output approach - Cortés-Borda, D.; Ruiz-Hernández, A.; Guillén-Gosálbez, G.; Llop, M.; Guimerà, R.; Sales-Pardo, M. (Energy policy, 2015)
Global warming mitigation has recently become a priority worldwide. A large body of literature dealing with energy related problems has focused on reducing greenhouse gases emissions at an engineering scale. In contrast, the minimization of climate change at a wider macroeconomic level has so far received much less attention. We investigate here how to mitigate global warming by performing changes in an economy. To this end, we make use of a systematic tool that combines three methods: linear programming, environmentally extended input output models, and life cycle assessment principles. The problem of identifying key economic sectors that contribute significantly to global warming is posed in mathematical terms as a bi-criteria linear program that seeks to optimize simultaneously the total economic output and the total life cycle CO2 emissions. We have applied this approach to the European Union economy, finding that significant reductions in global warming potential can be attained by regulating specific economic sectors. Our tool is intended to aid policy makers in the design of more effective public policies for achieving the environmental and economic targets sought. •We minimize climate change by performing small changes in the consumption habits.•We propose a tool that combines multiobjective optimization and macroeconomic models.•Identifying key sectors allows improving the environmental performance significantly with little impact to the economy.•Significant reductions in global warming potential are attained by regulating sectors.•Our tool aids policy makers in the design of effective sustainability policies.